THE EFFECT OF SERVICE QUALITY, PROMOTION AND PRICE PERCEPTION ON CUSTOMER LOYALTY AT THE BUMANTARA COFFEE SHOP IN SURABAYA CITY: THE EFFECT OF SERVICE QUALITY, PROMOTION AND PRICE PERCEPTION ON CUSTOMER LOYALTY AT THE BUMANTARA COFFEE SHOP IN SURABAYA CITY - Muhammad Septian Adi; Hery Pudjoprastyono (Management Science Research Journal, 2026)
This study aims to analyze the effect of service quality, promotion, and price perception on customer loyalty at Toko Kopi Bumantara in Surabaya. The research employs a quantitative approach, with data collected throughquestionnaires distributed to customers and analyzed usingthe Partial Least Square (PLS) method. The independentvariables include service quality, promotion, and priceperception, while the dependent variable is customer loyalty. The results indicate that service quality, promotion, and priceperception have a positive and significant effect on customerloyalty. These findings suggest that improving servicequality, implementing effective promotional strategies, andmaintaining favorable price perceptions can enhancecustomer loyalty sustainably.